The effect of experience economy on augmented reality-based marketing apps: a study of consumer satisfaction - Dian Martha Nurrul Amanah; Novinda Krisna Putri; Nurul Aini (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The objective of this paper is to examine the impact of the experience economy on augmented reality-based marketing apps and their influence on consumer satisfaction.Method — The research strategy employed in this study is a quantitative approach, utilizing survey methods. The primary data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The process of data collection encompassed the distribution of online questionnaires to participants who actively utilize smartphones. These participants were then required to engage with one of the five augmented reality marketing applications selected for this study: Shopee (Beauty Cam), Sephora (Virtual Artist), IKEA Place, Dulux (Visualizer), and Kinder Joy (Applaydu). To enhance the robustness of the findings, a total of 230 respondents were included in this study.Result — The study revealed that aesthetics have a positive influence on entertainment, learning, and escapism. Furthermore, entertainment, learning, and escapism have a positive influence on satisfaction.Contribution — The academic contribution of this study lies in its meticulous replication undertaken within a unique contextual setting featuring variations in subjects, objects, and research environments. This deliberate approach not only serves to reinforce the existing knowledge base but also elevates its applicability across diverse scenarios. The study's core scholarly merit emerges from its comprehensive exposition of the intricate mechanisms through which the augmented reality experience economy influences customer satisfaction, all situated within the distinctive socio-cultural and economic landscape of Indonesia.